2012
DOI: 10.2754/avb201281040339
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iodine from iodine-enriched alga Chlorella spp. on the pork iodine content and meat quality in finisher pigs

Abstract: The aim of the study was to evaluate the effects of iodine from iodine-enriched alga Chlorella spp. on the iodine content in pork and on meat quality traits in finisher pigs. Experimental feed mixtures were fed for a period of 3 months before slaughter. In group A (n = 12), the experimental feed mixture was supplemented with 2 mg I/kg in the form of iodine from iodine-enriched freshwater alga Chlorella spp. The experimental feed mixture for pigs in group B (n = 12) was supplemented with 2 mg I/kg in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
(17 reference statements)
2
14
0
Order By: Relevance
“…Similar results for meat quality traits were reported by Baňoch et al [45], who found that a 0.0002% level of incorporation of C. vulgaris in pig diets had no significant effect on color, pH, cooking loss and drip loss of pork. Here, the dietary incorporation of 5% C. vulgaris did not change pork quality traits and sensory parameters, which is very important for the consumer acceptance of this meat.…”
Section: Pork Quality Traits and Sensory Evaluationsupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results for meat quality traits were reported by Baňoch et al [45], who found that a 0.0002% level of incorporation of C. vulgaris in pig diets had no significant effect on color, pH, cooking loss and drip loss of pork. Here, the dietary incorporation of 5% C. vulgaris did not change pork quality traits and sensory parameters, which is very important for the consumer acceptance of this meat.…”
Section: Pork Quality Traits and Sensory Evaluationsupporting
confidence: 89%
“…We assessed, for the first time, the impact of a high dietary level (>2% in diet) of C. vulgaris, individually and combined with two exogenous CAZymes, on pig performance. In fact, some studies reported the use of C. vulgaris in pig diets but at much lower levels (1% in the diet or lower), compared with the 5% incorporated in the current trial [44][45][46]. Baňoch et al [45] investigated the effect of a very low level (0.0002%) of incorporation of C. vulgaris in female pigs, with an initial weight of 30 kg, and found no significant differences in ADG, HCW, lean muscle thickness and backfat thickness.…”
Section: Feed Intake Growth Performance and Carcass Characteristics mentioning
confidence: 86%
See 2 more Smart Citations
“…In Italy, mild iodine deficiency is rather common in many areas, despite the recent efforts to increase iodine intake, and therefore goiter and other iodine deficiency disorders are still observed (Olivieri and Vitti, 2014). As a preventive measure, salt iodization has been widely used; however, considering that the use of iodized salt is voluntary, additional measures for iodine deficiency prophylaxis are necessary (Baňoch et al, 2012). The iodine of milk and milk products represents the second-most important food source of the trace element in the European Union or in the United States (Bader et al, 2005), and its concentration in cow milk ranges between 30 and 300 μg/L (Moschini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%